Uniparental expression of ribosomal RNA in ×Festulolium grasses: a link between the genome and nucleolar dominance - Mahelka, Václav; Kopecký, David; Majka, Joanna; Krak, Karol (Frontiers in Plant Science, 2023)
Genome or genomic dominance (GD) is a phenomenon observed in hybrids when one parental genome becomes dominant over the other. It is manifested by the replacement of chromatin of the submissive genome by that of the dominant genome and by biased gene expression. Nucleolar dominance (ND) – the functional expression of only one parental set of ribosomal genes in hybrids – is another example of an intragenomic competitive process which, however, concerns ribosomal DNA only. Although GD and ND are relatively well understood, the nature and extent of their potential interdependence is mostly unknown. Here, we ask whether hybrids showing GD also exhibit ND and, if so, whether the dominant genome is the same. To test this, we used hybrids between Festuca and Lolium grasses (Festulolium), and between two Festuca species in which GD has been observed (with Lolium as the dominant genome in Festulolium and F. pratensis in interspecific Festuca hybrids). Using amplicon sequencing of ITS1 and ITS2 of the 45S ribosomal DNA (rDNA) cluster and molecular cytogenetics, we studied the organization and expression of rDNA in leaf tissue in five hybrid combinations, four generations and 31 genotypes [F. pratensis × L. multiflorum (F1, F2, F3, BC1), L. multiflorum × F. pratensis (F1), L. multiflorum × F. glaucescens (F2), L. perenne × F. pratensis (F1), F. glaucescens × F. pratensis (F1)]. We have found that instant ND occurs in Festulolium, where expression of Lolium-type rDNA reached nearly 100% in all F1 hybrids and was maintained through subsequent generations. Therefore, ND and GD in Festulolium are manifested by the same dominant genome (Lolium). We also confirmed the concordance between GD and ND in an interspecific cross between two Festuca species.